Niveles plasmáticos de citoquinas proinflamatorias en cáncer de próstata - López Fontana, Constanza Matilde (2019)
Prostate cancer has become an important public health problem affecting millions of men worldwide every year. Like other malignant tumors, prostate cancer shows evidence of a strong inflammatory component that is dependent on the release of pro-inflammatory cytokines,which might play a major role in the development and progression of the tumor, helping in its early stage, progression and aggressiveness. Aims: The goal of this study was to determine the relationships between the serum levels of pro-inflammatory cytokines and the different stages of prostate cancer. To this end, sera from patients enrolled by The Laboratory of Metabolic Diseases and Cancer of the Faculty of Pharmacy and Biochemistry at the University Juan Agustín Maza in Argentina, were analyzed through ELISA and their pro-inflammatory cytokines (IL-6, TNF-α and MCP-1) quantified. Patients were first classified into three groups (Control, at Risk, and Cancer subjects) and anthropometric, biochemical and histological parameters of prostate were then determined for all groups. Results and Conclusions: Despite displaying elevated serum concentrations of IL-6 and TNF-α in the Cancer and the Risk groups compared to the Control group, the differences did not reach significance. However, there was a positive correlation between these cytokines only in the Risk and Cancer groups, showing a general inflammatory behavior in these patients. The results obtained provide general data about the behavior of pro-inflammatory cytokines in prostate cancer. However, they do not demonstrate a direct correlation betweenserum levels and neoplastic progression. Nevertheless, these findings do not rule out a possible relationship between prostate cancer and serum levels of pro-inflammatory cytokines.